Crop production intensity and haNDVI indicator – amplitude of NDVI related to harvest - Łopatka, Artur; Koza, Piotr (Polish Journal of Agronomy, 2020)
In response to the growing needs of spatial recognition of the intensity of agricultural crop production, a new haNDVI indicator was developed, that measures the amplitude of the NDVI indicator related to the harvest. The proposed way of calculating haNDVI is to use the minimum and maximum functions for the raster layers set from the growing season. This avoids the need for preliminary classification of crops, including to determine the moment of harvest. It has been shown that the haNDVI indicator calculated on aggregated NDVI layers with a resolution of 1 km is correlated with soil quality indexes, NPK fertilization intensity (r = 0.69) and the share of crops in the total area (r = 0.86) for municipalities. The properties of the haNDVI indicator make it particularly useful for the initial, rapid scanning of environmental quality in terms of the intensity of plant production and indicating the hazards locations associated with the use of fertilizers and plant protection products.